The effect of litter size and piglet sex on the gestation length of Landrace-Duroc crossbred pigs - Olivia Claudya Lalo; Tarsisius Considus Tophianong; Yustinus Oswin Primajuni Wuhan; Heny Nitbani (Ovozoa: Journal of Animal Reproduction, 2026)
This study was conducted to determine and identify the effect of litter size and piglet sex of on the gestation length of Landrace-Duroc crossbred pigs. Fifteen sows from the Manufarm farm in East Kupang district, Kupang regency, East Nusa Tenggara, Indonesia, were used in this study and were bred using artificial insemination (AI). Data were collected using a purposive sampling method based on certain criteria. Both primary and secondary data were utilized. Primary data were obtained through surveys, observations, and interviews, while secondary data were obtained from the farmers' data records. The research variables observed in this study included litter size, piglet sex, and gestation length. The data obtained were analyzed using Spearman's correlation test to examine the correlation between litter size and piglet sex with gestation length in Landrace-Duroc crossbred pigs. The results showed that the average litter size was 10.4 ± 0.986 piglets, consisting of 5.0 ± 1.852 males and 5.4 ± 1.882 females. The gestation length ranged from 111 to 114 days, with an average of 112 ± 0.926 days. The results of the Spearman correlation analysis showed that litter size was not significantly correlated with gestation length (p >0.05). Similarly, piglet sex showed no significant correlation with gestation length for both male (p >0.05) and female piglets (p= 0.254; p >0.05).